(untitled) (Carte Romanze, 2019)
The poetic lament is part of Portuguese literary tradition, as demonstrated by both the trobadour songs and the court poems collected by Garcia de Resende in Cancioneiro Geral (1516). Luís Anriques is author of two poems dedicated to the death of Prince D. Afonso (1491) and King D. João II (1495). The paper aims to analyze the content and formal characteristics of the two texts and in particular the recurrent motifs that make explicit their belonging to the literary genre of funeral elegy.